Uninsurable Risks of Floods, Deluges, Overflows and the System of Solution - Hana Bártová; Karel Hanzlík (European Financial and Accounting Journal, 2013)
Uninsurable risks have significant impact on expenses of private and public sectors of economy. In spite of several commercial insurance products and high quality of insurance services current trend of insurance industry is set to define exceptions of insurance protection. The highest losses caused by realization of uninsurable risks in the Czech Republic are constituted by consequences of floods, deluges and overflows. Recent history of flood occurrence emphasizes insufficiency of prevention, protection and loss solution. Due to these risk factors we have focused our research on issues of uninsurable risks in conditions of the Czech insurance market. The system solution is based on fund approach to ensure commercial insurance protection. Multi-Source System Solution of Uninsurable Risks is purposed in the form of fund with participation of the state authority. Our solution depends on pool creation and primarily should cover enormous claims development. Assumption of fund profitability encourages insurer motivation to become a pool member. Important part of research represents calculation of gross premium. Assessment of input data and calculation of premium are based on real published data and conform to real market development in the Czech Republic. Calculations are also based on our estimations of risk development. This research highlights the importance of uninsurable risks solution. Effective instrument able to protect lives and property is an innovative commercial insurance product. Our commercial solution is a way to strengthen the role of insurance in a field of uninsurable risks. The system solution is designed to conditions of the Czech insurance market and takes into account special domestic factors. We suppose that our solution is possible to be adopted in conditions of any insurance market in case of relevant data and risk factors using.
Keywords: G22; G28; P11; R11; 650; Flood; Flood fund; Gross premium; Insurance pool; Uninsurable risk.